Phenotypic and genotypic variation in tenera progenies derived from different sources of dura crossed with avros pisifera - Mohamed, Mohaimi (2012)
This study was executed to search for new breeding strategies to be employed towards the improvement of elite Deli duras populations from Breeding Population of Restricted Origin (BPRO). The objectives for the study were (i)to estimate phenotypic and genetic variances and heritabilities (broad-sense and narrow sense) in various dura populations crossed to AVROS pisifera, (ii)to estimate phenotypic and genotypic coefficients of variation of the characteristics measured, (iii) to estimate phenotypic correlations among quantitative traits, and (iv) to identify for the characteristics that are unique to each of these dura sources crossed with AVROS pisifera. Three experiments each consisted of 17, 45 and 15 duras crossed with AVROS pisifera progenies. The Deli duras originated from various sources of Deli dura BPROs consisted of Ulu Remis dura, Johor Labis dura and their derivatives. Experiment 1 and Experiment 2 utilized North Carolina Mating Design I while Experiment 3 utilized the bi-parental crosses. All experiments were laid out in Randomised Completely Block Design (RCBD) with four replications and were planted at 8.8m triangular on coastal clay-loam soil in East Estate, Carey Island. Due to high selection pressure in most of the dura populations during their early improvement programmes certain characters found to be more concentrated in different dura populations. It is possible to combined two different desirable characters from two different dura populations and combinations of more than two characters can be carried out by utilizing a three-way crosses. The proposed strategies were supported by the analysis that showed some of these characters can result in the improvement of desirable economic characters. The improvement of dura population was proposed based on results that showed low male effect in females parents in most of the economic characters indicated there was higher genetic control in female parents for most of the traits. The strategies can be more viable and the improvement can be made faster by combining characters based on the heritabilities and correlation results from the studies. Results obtained in all experiments showed that different selection and breeding objectives can accumulate different set of characters and intercrossing among these duras can be carried out towards further yield improvement in oil palm.